Profile of CT Scans of Petrous Bones at the UHC-Campus of Lomé - Judith Edwige Guiaba Kette Mokpondo; Francky Kouandongui Bangue Songrou; Timothee Mobima; Chrispin Euloge Tapiade; Christ Borel Tambala; Aime Stephane Kouzou; Heritier Yannick Sombot Soule; Lantam Sonhaye; Victor Adjenou (European Scientific Journal, ESJ, 2025)
Introduction: the purpose of this work was to determine the profile of CT scans of petrous bones, to list the indications, to describe the techniques of realization and the pathological aspects of CT scans observed. Methods: this was a prospective and descriptive study carried out over a period of 6 months concerning the CT scans of the petrous bone carried out in the radiology department of the UHC-Campus at Lomé. The parameters studied concerned epidemiological data and lesions observed on computed tomography. Results: we had performed 34 CT scans of the petrous bons or 0.5%. Interns, specialty doctors and ENT doctors were the main prescribers in 58.8% and 32.4% respectively. Patients came more from emergency departments (50%). All age groups were concerned with a predominance of those 21-40 years (23.5%). The male sex was predominant with a sex ratio of 2.1. Drivers were more represented (23.5%). The most frequent indication was petrous bone trauma (44.1%) and road accidents were the leading cause (73.3%). The examination was performed in all cases without injection of the contrast and was pathological in 70.6% mainly in trauma, conductive hearing loss, chronic otitis media, EAC stenosis and pulsatile tinnitus. The main traumatic injury found was extralabyrinthine fractures (91.7%). Incudo-malleus dislocation was the main ossicular lesion found (25 %). The hemotympanum was found in 83.3%. CT was normal (29.4%) in vertigo/tinnitus, mixed deafness, conductive hearing loss/tinnitus, earache and non-traumatic facial paralysis. Conclusion: computed tomography remains the first  choice examination in the exploration of petrous bone trauma, conductive hearing loss and chronic otitis media. On the other hand, it occupies a limited place in the exploration of vertigo / tinnitus as well as non-traumatic facial paralysis.